Mundkur Memorial Award Lecture - Current status and future approaches for management of groundnut diseases in India - MAYEE, C.D. (Indian Phytopathology, 2002)
Groundnuts are being grown increasingly under irrigation in India. It is therefore important to monitor new disease problems. Work has been undertaken to develop disease management strategies. Details of cultural, legislative, biological and chemical control methods are described along with details of resistant plants and breeding programmes.